Socialistic Brands A Unique Category of Vintage Brands - Rogowski, Mikolaj (Munich Intellectual Property Law Center - MIPLC, 2017)
Socialistic brands are signs with unique characteristics acquired through their use in particular historical circumstances. It is considered whether, decades after the fall of the iron curtain, the shared historical pedigree justifies different treatment of these signs. The author attempts to answer the question of what would constitute as unfair appropriation of these brands and discusses the availability of legal remedies in such cases. The analysis of issues relating to socialistic brands is conducted on the basis of European and Polish law and jurisprudence. Trademark law and other fields of intellectual property law form the core of this consideration. The author additionally employs findings from branches of social sciences such as anthropology, sociology and semiotics, in order to shed light on the complex nature of the attractiveness of signs and how cultural connotations affect it.